Radiofréquences et santé : améliorer l’évaluation des risques - Olivier Merckel; Johanna Fite; Olivia Roth-Delgado (VertigO)
The constantly changing of wireless technologies applications using radiofrequencies is accompanied by questions, both from the people who use or are exposed to them, as from researchers. This paper aims to explore the regulatory changes, which apply, to wireless technologies in terms of the development of knowledge related to exposure to radiofrequency electromagnetic fields and health effects that could be associated. The regulatory framework in this area can be seen as a reflection of scientific knowledge and uncertainties, which is translated into provisions coming from EU law or application of the precautionary principle, for example. Although public controversy around the issue of health effects of exposure to electromagnetic fields do not necessarily reflect their associated levels of scientific evidence, they have pushed to strengthen the structuring and description of risk assessment methods in this domain. This effort helps to bring out the types of scientific uncertainty accompanying risk assessments (lack of knowledge, conflicting data, etc.) and thus refines management provisions or potential regulatory changes.